Tiếp cận đa giác quan và dạy học viết văn miêu tả ở tiểu học theo hướng tiếp cận đa giác quan - Phan, Thị Hương Giang; Trần, Thị Quỳnh Nga (Tạp chí Giáo dục, 2024)
The multisensory approach is a modern teaching trend that has been implemented in many countries around the world. This teaching strategy aimed at stimulating learners' senses has shown positive impacts in the teaching process across many different subjects. In the field of writing, multi-sensory teaching activities are also being studied and tested for effectiveness. This article presents some theoretical issues about the multisensory approach and the characteristics of descriptive writing to set a basis for applying this approach to teaching descriptive writing in primary schools. This is an appropriate direction in teaching Vietnamese in primary schools, meeting the requirements of developing learners' competence in the context of the 2018 General Education Curriculum for Literature.